Mikrochirurgie a mikromanipulace v lécbĕ muzské infertility: výsledky rocního sledování - Kocí, K; Lachman, M; Mayer, Z; Mrázek, M; Jarolímková, K; Teplá, O; Míka, J; Nejezchlebová, L (Rozhledy v chirurgii, 1998)
A one-year study of 51 infertile couples, 47 couples evaluated--25 cases of testicular azoospermia and 22 cases of obstructive azoospermia. The mean age of the men in the group is 33 years (22-48 years). The follow-up period is 1-18 months. In 17 instances microsurgical epididymal sperm aspiration--MESA was made, five times testicular sperm aspiration--TESA and in 25 men testicular sperm extraction--TESE was used. In the group with testicular azoospermia it proved possible to obtain sperm in 12/25 cases, i.e. in 48%. In men with obstructive azoospermia all aspirations were successful, i.e. the yield was 100%. In this group five infants were born, another seven pregnancies are under way. Thus regardless of the etiology of male infertility 12/47 cases, i.e. 25.5%, were successfully resolved. When using differentiated evaluation of the two groups the results are as follows: in the group with testicular azoospermia one infant were born and five pregnancies are under way, i.e. 40.9%.
Keywords: dospělí; lidé středního věku; Humans; Micromanipulation; mikrochirurgie; ženské pohlaví; mužské pohlaví; oligospermie; mužská infertilita; Middle Aged; Adult; Reproductive Techniques; Male; těhotenství; reprodukční techniky; Pregnancy; Infertility, Male; Oligospermia; Microsurgery; lidé; mikromanipulace; Female